Development of fluorometric reactive oxygen species assay for photosafety evaluation. (August 2016) - Seto, Yoshiki; Ohtake, Hiroto; Kato, Masashi; Onoue, Satomi
Abstract: The present investigation involved an attempt to develop a new reactive oxygen species (ROS) assay system for the photosafety assessment of chemicals using 1, 3-diphenylisobenzofuran (DPBF), a fluorescent probe for monitoring ROS generation. The assay conditions of the fluorometric ROS (fROS) assay were optimized focusing on the solvent system, concentration of DPBF, fluorescent determination, screening run time and reproducibility. The photoreactivity of 21 phototoxic and 11 non-phototoxic compounds was assessed by fROS assay, and the obtained ROS data were compared with the results from a micellar ROS (mROS) assay and in vitro / in vivo phototoxicity information to confirm the predictive capacity of the fROS assay. In the optimized fROS assay, intra-day and inter-day precision levels (coefficient of variation) were found to be below 5%, and the Z'-factor for DPBF fluorescence quenching showed a large separation between positive and negative controls. Of all tested compounds, 3 false positive and 7 false negative predictions were observed in the fROS assay, and the negative predictivity for the fROS assay was found to be lower than that for the mROS assay. Although the fROS assay has some limitations, the procedures for it were highly simplified with a marked reduction in screening run time and one analytical sample for monitoring ROS generation from compounds. The fROS assay has the potential to become a new tool for photosafety assessment at an early stage of product development. Highlights: Reactive oxygen species (ROS) assay has operational complexity and a long run time. Fluorescent ROS (fROS) assay was developed for improving these drawbacks of the ROS assay. Although only a few false negative were observed, the fROS assay could simplify assay procedures with enhanced productivity. Upon further improvement on fluorescent probe, the fROS assay would provide for photosafety assessment of chemicals.